Interdisciplinary management of a mutilated Class II division 1 malocclusion with deep bite and missing first molars using a modified MUST appliance - A Case Report (Orthodontic Journal of Nepal, 2020)
Introduction: Orthodontic management of cases presenting with compromised permanent first molars are difficult in aspects of treatment due to the loss of anchor teeth. Therefore, a problem-oriented approach is always preferred as an aid in treatment line.Description: In this report, we discuss a case with multiple orthodontic problems ie. Class II division 1 malocclusion, deep bite, crowding and grossly decayed first molars of all four quadrants. The management of this case was done using a modification of the MUST appliance for uprighting the lower molars and closure of molar extraction spaces.Results: The total treatment duration was 23 months and results were stable after a 1 year follow up.Conclusion: Correct diagnosis and effective biomechanics are the key to successful treatment of compromised dentition.